The Effect of Net Interest Margin (NIM), Operating Expenses, Operating Income (BOPO), Loan to Deposit Ratio (LDR), on Return on Assets (ROA) at PT Bank Mayapada Internasional Tbk for the Period of 2014-2023 - E Landitha Karunia Antika; Palupi Permata Rahmi; Yoyo Sudaryo; Riyandi Nur Sumawidjaja; Diah Febriyanti (Syntax Idea)
Profitability is a ratio to assess the company's ability to seek profit. This ratio also provides a measure of the level of effectiveness of a company's management. Profitability at PT Bank Mayapada Internasioanl Tbk in 2014-2023 fluctuated every year and tended to decline at the end of the research year. This study aims to determine the effect of Net Interest Margin (NIM), Operating Costs of Operating Income (BOPO), Loan to Deposit Ratio (LDR) on Return On Assets (ROA) for the 2014- 2023 period. This study uses a quantitative method with a descriptive verification approach. The data source used is secondary data with documentation data collection inthe form of annual financial reports and purposive sampling technique. The data analysis technique used is descriptive analysis, regression analysis, correlation analysis, coefficient of determination analysis, and hypothesis testing either partially or simultaneously with the help of the SPSS 25 program. The research results show that the average ROA is 0.919%, categorized as healthy. However, ROA in the last 2 years of the 2022-2023 research period has decreased drastically with the lowest value being 0.04% and is below Bank Indonesia's provisions for the healthy ROA category, namely 1.5%. The average NIM is 3.13% which is categorized as healthy, but in the year of research, namely 2020, it dropped drastically with a minimum value of 0.47%, even far from the minimum limit of 6% according to Bank Indonesia regulations for the healthy NIM category. The average BOPO is 91.79 which is categorized as healthy, but BOPO at the end of the research period in 2024 rose to the highest value, namely 99.40% and is above Bank Indonesia's provisions for the healthy BOPO category, namely a maximum of 85%. The average LDR is 85.10% which is categorized as however the LDR in the 3 years at the end of the research period in 2021 has decreased drastically with the lowest value being 71% and the highest value in 2019 even approaching the maximum and minimum limits, namely 80%-110% accordingly. Bank Indonesia provisions for the healthy LDR category. Partially NIM has no effect on ROA with a contribution of1.80%. BOPO has no effect on ROA with a contribution of 99.40%. LDR has a significant effect on ROA with a contribution of 88.59%. Together (simultaneously) NIM, BOPO, LDR have a significant influence on ROA at PT Bank Mayapada Internasional Tbk for the 2014-2023 period.